Analysis of the frequency of cesarean sections, vaginal interventions and birth canal injuries in various methods of anesthesia during labor - Michał Michalczyk; Dorota Torbé; Andrzej Torbé (Kazimierz Wielki University, 2018)
Aim: The aim of this study was to analyze and compare the frequency of cesarean sections, vaginal interventions and birth canal injuries in various methods of anesthesia during labor. Material and methods: 160 pregnant women ≥ 37 weeks, which attempted vaginal delivery in the Department of Obstetrics and Gynecology of the Pomeranian Medical University in Szczecin, were divided into four groups: 1. PCEA (n = 40) women giving birth under patient-controlled epidural anesthesia (PCEA) in a horizontal position; 2. Pethidine (n = 30) women giving birth subjected to analgesia by parenteral supply of pethidine; 3. Fentanyl (n = 30) women giving birth subjected to analgesia by parenteral supply of fentanyl; 4. Control (n = 60) women giving birth without analgesia. In each group the frequency of intrapartum caesarean sections, episiotomies, injuries of birth canal and of uterine revision was evaluated. Results: No significant differences in the incidence of completion of delivery by cesarean section between the studied groups of women was observed. Also the incidence of minor injuries of birth canal was comparable. Analysis of the frequency of episiotomies and of postpartum instrumental control of uterine cavity showed no significant differences between the studied groups. Conclusions: Both, the use of epidural analgesia in the formula PCEA and parenteral use of an opioid analgesics during delivery, do not affect the frequency of completion of labor by caesarean section, the incidence of injuries of the birth canal, the incidence of instrumental inspection of the uterine cavity and are not associated with an increased risk of episiotomy.